On the role of a Rossby wave train during the extratropical transition of hurricane Helene (2006). (14th June 2012) - Pantillon, F.; Chaboureau, J.‐P.; Lac, C.; Mascart, P.
Abstract Three successive interactions of hurricane Helene (2006) with a Rossby wave train during the extratropical transition of Helene over the North Atlantic were investigated. Numerical experiments were performed with different horizontal resolutions and configurations, over a domain that stretches from the eastern Pacific to the Western Mediterranean to encompass Helene and the whole Rossby wave train. In particular, a cloud‐resolving run offered an explicit representation of strong diabatic effects involved in the three successive interactions. While the circulation and moisture anomaly of Helene were essential to its own reintensification, it is shown that the Rossby wave train played an important role in the track and intensity of Helene and in explosive cyclogenesis downstream. First, the Rossby wave train steered Helene in such a way that a small difference in phasing resulted in large errors in the track of Helene. Only a run at kilometre scale was able to correctly forecast the 5‐day track of Helene. Second, through the formation of three filaments, the Rossby wave train created a quasi‐diurnal cycle in the intensity of Helene. Helene responded with strong diabatic activity that prevented the superposition of an upstream trough and enhanced a downstream ridge. Finally, model errors in the outflow of Helene propagated downstream with the group speed of the Rossby wave train, leading to the loss of predictability of a tropical‐like cyclone over the Mediterranean. This study suggests that, in addition to the horizontal resolution, uncertainty from the model microphysics and from initial conditions need to be characterized to improve mid‐range forecast downstream from an extratropical transition. Copyright © 2012 Royal Meteorological Society